Digital gamification in preschool learning: a systematic review of the literature - Marcillo Vera, Fabricio Rolando; Hernández, Wilmar; Torres, Jimmy; Cusme, Lorena; Mora, Eugenio; Cobeña, Susana (Enfoque UTE, 2023)
In the educational context, gamification has emerged as an effective strategy to enhance learning and motivation. With the rise of information and communication technologies, digital gamification (DG) has emerged. Although there are numerous studies summarizing the contributions of gamification in education, very few have included preschool education. The present systematic review, supported by 25 primary studies published between 2014 and 2022 and indexed in Scopus and Web of Sciences, seeks to close this gap by characterizing the main contributions, and qualitatively synthesizing the effects of DG. The results indicate that there is a growing interest in the topic, where most of the studies originate in Asia; they are published in journals; and are based on the proposal of video games for computers or mobile devices that seek to improve language learning. Narrative approach research predominates, based on samples of less than 10 participants, employing Achievement (Progression) type game elements. The 15 studies that measured the effect of DG report positive results.